METHODICAL ASPECTS OF EFFECTIVENESS EVALUATION EXPENDITURE BUDGET FOR PROVIDING COMPREHENSIVE SERVICES IN VIEW OF THEIR INSTITUTIONAL FEATURES - E. Yu. Elistratova (Модернизация, инновация, развитие, 2017)
The article presents the author developed a methodological approach for assessing the eff ectiveness of budget expenditures for the provision of general education services, treating them as institutionally significant costs that impact on the development of the social environment. The proposed methodology the author evaluate the eff ectiveness of budget expenditures to evaluate the economic and incl socio-economic efficiency of budget spending. Having considered the proposals by the author of the budget appropriations allocation approach, taking into account the results of the use of budget funds in the sphere of general education.The purpose / objectives of the work: the development of methodology to assess the effectiveness of budget spending in education with a view to improving the management and efficiency of educational organizations.Conclusions / relevance. The practical significance of the results of the study is to develop a unifi ed scheme of evaluating the eff ectiveness of budget expenditures and improve the quality of their management. The measures that allow to establish a direct link between the budget allocated and performance indicators of educational institutions. The proposed algorithm in the article can be used in the practice of the authorities related to the management of public expenditure in the current conditions.